Pengaruh Keputusan Investasi, Keputusan Pendanaan dan Kebijakan Deviden terhadap Nilai Perusahaan (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2012-2015) - Amanda Putri, Novia, Dra. Wuryaningsih Dwi Lestari, MM (2017)
This research aimed to analyze the influence of investment decisions (PER), financing decisions (DER) anddividend policy (DPR), to corporate value (PBV),in a manufacturing companies which listed in Indonesian Stock Exchange (BEI) in the period 2012 to 2015. The research sample consisted of 22 companies of 143 in a manufacturing companies listed on BEI by the observation numbers of 88 observational data. The sampling method was done by using purposive sampling. The researched data was obtained from ICMD and IDX. The data analysis technique used in this research is multiple linear regression. Hypothesis testing using t statistics used in this research to test the partial regression coefficients as well as fstatistics to test the significance of the influence together, with the level of significance of 5%. Other than that, all the variables had been tested with the Normality test, Multicollinearity test, Autocorrelation test,and Heteroskidastity test. The results showed that all variables passed the classical assumption test and suitable to be used as research data. T-test statistical indicated that investment decision (PER), financing decision (DER), and devidend policy (DPR)has significant influence on corporate (PBV). Keywords: investment decisions (PER), financing decisions (DER), dividend policy (DPR), corporate value (PBV)